Analysis of Locomotor Movement Skills in Students with Down Syndrome at SLBN-A Citereup, Cimahi City - Azzahra, Irene Kanafika; Nugraha, Reshandi; Gumilar, Agus (JUMORA: Jurnal Moderasi Olahraga, 2025)
There is limited information available regarding special education in Indonesia. Nonetheless, the development of motor skills is crucial for students with Down syndrome in an inclusive educational setting. Purpose: This research aims to assess the fundamental locomotor skills of students with Down Syndrome and to explore whether there are differences in motor performance based on sex. Method: A descriptive quantitative approach was employed, with a sample of 20 students, consisting of 10 males and 10 females with Down Syndrome. The Test of Gross Motor Development-2 (TGMD-2), created by Ulrich (2000), served as the evaluation tool. Data were analyzed using descriptive statistics and independent samples t-tests, utilizing SPSS version 29.0 and Microsoft Excel software. Results: The subtest component of jumping achieved the highest mean score (M = 4.1, SD = 1.944), whereas hopping showed the lowest performance (M = 2.35, SD = 1.182). About 70% of participants (n = 14) displayed average basic locomotor movement skills. Overall, there were no significant differences in locomotor movement skill performance based on gender (p = 0.195 > 0.05). Conclusion: Students with Down Syndrome showcase a range of skill levels across different movement abilities, with jumping identified as one of their strengths that requires intervention. The outcomes of this study aim to establish a valuable database regarding the locomotor skill profiles of students with Down syndrome in Indonesia, which is pertinent to inclusive education, and to provide a fresh perspective on the exploration of gender-related locomotor skills